Rheology and thermal conductivity of non-porous silica (SiO2) in viscous glycerol and ethylene glycol based nanofluids - Akilu, S. (Elsevier Ltd, 2017)
Nanofluids are advanced fluids with novel properties useful for diverse applications in heat transfer. This article reports the experimental determination of thermal conductivity and viscosity for silica (SiO2) nanofluids in ethylene glycol (EG) and glycerol (G) as base fluids. A two-step method was applied to disperse the nanoparticles in the base fluids for the particle volume concentration of 0.5–2.0. The dispersion stability of the nanofluids was evaluated by zeta potential analysis. All the measurements were performed in the temperature interval from 30 °C to 80 °C. It was found that the thermal conductivity increases with temperature. The SiO2-EG showed higher conductivity enhancement than SiO2-G nanofluids. Rheological analyses confirm Newtonian behavior for silica nanofluids within shear rate range of 20–100 s− 1. Viscosity decreases with an increase in operating temperature. The SiO2-EG demonstrated very weak temperature dependence compared to the SiO2-G nanofluids. Based on these measured properties, the criterion for heat transfer performance was determined. Furthermore, equations have been proposed with accuracy within ± 10 deviations to predict the thermal conductivity and dynamic viscosity of EG and G-based SiO2 nanofluids. © 2017 Elsevier Ltd